Overdosing on Junkie: `Heroin is a cruel mistress' in gritty documentaries: Final Edition - Lepage, Mark (The Gazette (Montreal), 1999)
"Everybody has some kinda jones in New York City." John Spacely speaks from no small experience. The narrator and star of Lech Kowalski's 1983 documentary Story of a Junkie is as real as an overdose. When not shooting heroin on camera, he is talking about shooting heroin or trying to buy it. Spacely is the genuine article, which is to say, the personification of a fraudulent lifestyle that has reduced living to mere existence. He wears an eyepatch, the result (we learn) of a chain-beating from a pack of drag queens. He leads Kowalski's cameras on a tour of the demi-monde, among the jabbering, slurring zombies of street mercantilism. Along the way, he explains how an apparently sweet kid from California found himself in the zero-sum game of heroin addiction. The selling point of Junkie is Kowalski's access to his subject(s). There is footage of a mugging, wherein Spacely is relieved of his beloved skateboard. A man is gut-shot in a street dispute; another is stabbed. In this world, women sit around a table discussing personal responsibility, which has been reduced to remembering to buy cigarettes as well as heroin. Throughout, Spacely narrates, runs, pawns, buys, cooks, ties off his arm and injects with numbing repetition, in bedrooms and galleries and toilet cubicles.